Electricity Storage: The Main Pillar of Energy Security - Cruceru, Alin E.; Popescu, Florin G.; Fita, Daniel N.; Marcu, Marius D.; Olteanu, Razvan C.; Schiopu, Adrian M.; Popescu, Gabriela (Scientific Research, New Technologies and Applications Vol. 10, 2024)
Electricity storage has emerged as a critical component in ensuring energy security in the transition to a sustainable and resilient energy system. With the increasing reliance on renewable energy sources such as solar and wind, characterized by intermittent and variable output, storage technologies are vital to balancing supply and demand, enhancing grid stability, and mitigating energy shortages. This paper explores the pivotal role of electricity storage in bolstering energy security, highlighting its ability to decouple energy generation from consumption, provide backup during outages, and reduce dependency on fossil fuels. Advances in storage technologies, including lithium-ion batteries, flow batteries, and emerging solutions like solid-state batteries and hydrogen storage, are examined in terms of efficiency, scalability, and cost. Additionally, the integration of storage with decentralized energy systems and smart grid innovations is discussed as a strategy to enhance resilience against cyber threats and natural disasters. The challenges of scaling up storage—such as resource constraints, recycling, and regulatory frameworks—are analyzed, along with the potential for technological breakthroughs to overcome these barriers. Ultimately, electricity storage is positioned not just as a supporting technology but as a foundational pillar of energy security in the 21st century, enabling reliable, clean, and equitable energy access.